(untitled) (Global Journal of Human-Social Science, 2021)
Using Mexico’s Social Cohesion Survey for the Prevention of Violence and Crime (ECOPRED 2014) and the Mexican Intercensal Population Survey (CONTEO 2015) this paper analyses the characteristics and environment factors that influence the violent behavior of young people aged 14 to 24 years within the 47 largest Mexican cities. The existence of spatial correlation between Mexican cities is corroborated and after controlling for it, it is found that factors related to addictions (drug use by young people and their families) and a violent environment around the young (being bullied, robbed, or having violent friends, neighbors, coworkers or classmates) are positively related to the percentage of young people who shout, hit objects, hit people, carry weapons, or have been arrested. Public policies to reduce the use of drugs and to improve the environment where young people live, mainly in their neighborhoods, schools and jobs, will have a direct effect on reducing the violent behavior of young people. And given the confirmed existence of spatial effects, coordinated efforts between nearby cities could multiply the impact of such public policies.